CT and MR Imaging of Hepatocellular Carcinoma and Liver Cirrhosis - Masahiro Okada; Ryoji Aoki; Yujiro Nakazawa; Kenichiro Tago; Kazushi Numata (Gastroenterology Insights)
Liver masses are routinely evaluated using ultrasonography (US), computed tomography (CT), and magnetic resonance imaging (MRI). MRI may be used for further investigation in cases with atypical findings and difficult diagnoses. Hepatocellular carcinoma (HCC) is a common malignancy, and it is important to know the exact spread and number of HCCs, as there are numerous treatment options. In addition, it is important to know how the differentiations of HCCs are reflected on the images, and what the subtypes of HCCs look like on the images. Elastography with US and MRI is increasingly used to measure liver stiffness, and non-invasive assessment of liver fibrosis is also possible. This review describes the diagnosis of HCC on commonly used CT and MRI, and also touches on the frontiers of imaging diagnosis of liver parenchymal changes such as liver cirrhosis.